Composition of transcription factor B-TFIID. - Timmers, H T (1992)
Initiation of transcription by RNA polymerase II requires a TFIID factor, which can recognize the TATA element common to many promoters. Two distinct multisubunit TFIID factors can be resolved from extracts of mammalian cells, and both of them contain the well-characterized TATA-binding protein (TBP) and are capable of supporting RNA polymerase II transcription in an in vitro reaction system. The smaller complex, B-TFIID, was purified and its subunit composition was determined. B-TFIID consists of two subunits: the TBP and a TBP-associated factor (TAF) of 170 kDa. This TAF is specific for B-TFIID and appears not to be present in the D-TFIID complex. Furthermore, it was found that the highly purified B-TFIID fractions have (d)ATPase activity.